Epidemiology of Acute Injuries in Surfing: Type, Location, Mechanism, Severity, and Incidence: A Systematic Review - Katherine McArthur; Darcy Jorgensen; Mike Climstein; James Furness (MDPI AG, 2020)
Prospective and retrospective studies have examined traumatic injuries within competitive and recreational surfers worldwide using online surveys and health care facility (HCF; e.g., hospital, emergency department, medical record) data. However, few studies have provided a synthesis of all available literature. The purpose of this study was to obtain, critique and synthesise all literature specific to acute surfing injuries, and evaluate differences in injury type, mechanism and location between HCF and survey data. A systematic literature review design was used to identify relevant articles from three major databases. Peer-reviewed epidemiological studies of musculoskeletal surfing injuries were included. A modified AXIS tool was used for critical appraisal, and objective data was extracted and synthesized by lead researchers. Overall frequencies for injury location, type and mechanism were calculated from raw injury data. A total of 19 cross-sectional articles of fair to good quality (Modified AXIS 54.2−83.3%) were included in this study; 17 were National Health and Medical Research Council (NHMRC) level III-2 (retrospective) and two were level II (prospective). Articles examined competitive, recreational and combined populations. Injury data from Australia, Brazil, UK, USA, Portugal, Japan, Norway, and worldwide were represented. Skin (46.0%; HCF 50.1%, survey 43.8%) and being struck by own surfboard (38.6%; HCF 73.4%, survey 36.7%) were the most common injury type and mechanism. Head, face and neck injuries were most common in HCF (43.1%) versus lower limb injuries (36.4%) in survey data. Incidence proportion was highest in aerialists (0.48). Incidence rate (number of injuries per 1000 h) ranged from 0.74 in Australian surfers (Melbourne) to 6.6 in international contest surfers from medical record data. This review highlights the prevalence of skin, board-related, head, face and neck, and lower limb surfing injuries across available literature. Proposed use of protective equipment and foam-based surfboards in dangerous or crowded surf locations may reduce injury risk.